2019
DOI: 10.1021/acsomega.8b03175
|View full text |Cite
|
Sign up to set email alerts
|

Induced Lanthanide Circularly Polarized Luminescence as a Probe of Protein Fibrils

Abstract: Protein fibrils are involved in a number of biological processes. Because their structure is very complex and not completely understood, different spectroscopic methods are used to monitor different aspects of fibril structure. We have explored circularly polarized luminescence (CPL) induced in lanthanide compounds to indicate fibril growth and discriminate among fibril types. For hen egg-white lysozyme and polyglutamic acid-specific CPL, spectral patterns were obtained and could be correlated with vibrational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Empirically, five VCD signature bands in the amide I (C=O stretching, ∼1650 cm −1 ) and amide II (CN stretching, ∼1530 cm −1 ) regions were ascribed to amyloid fibril aggregation, but VCD patterns of different signs and shapes were found for various proteins and peptides . Even for the same protein, a slight variation in fibril preparation may significantly affect their morphology and VCD …”
Section: Vibrational Circular Dichroismmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirically, five VCD signature bands in the amide I (C=O stretching, ∼1650 cm −1 ) and amide II (CN stretching, ∼1530 cm −1 ) regions were ascribed to amyloid fibril aggregation, but VCD patterns of different signs and shapes were found for various proteins and peptides . Even for the same protein, a slight variation in fibril preparation may significantly affect their morphology and VCD …”
Section: Vibrational Circular Dichroismmentioning
confidence: 99%
“…[95][96][97][98][99] Even for the same protein, a slight variation in fibril preparation may significantly affect their morphology [100] and VCD. [101][102][103][104][105] For example, different polymorphic forms of hen egg-white lysozyme, apo-α-lactalbumin, TTR peptide and HET-s prion protein were formed at different pH. [98] Figure 1 illustrates how IR and VCD spectra of hen egg-white lysozyme fibrils grown at various pH levels correlate with SEM and fluid-cell AFM microscopy images for two fibril types.…”
Section: Vibrational Circular Dichroism Enhanced By Molecular Condensmentioning
confidence: 99%
“…The polymorph grown from non‐seeded solutions exhibited a negative vibrational circular dichroism (VCD) in the amide I region, with the dissymmetry factor ( g , VCD to absorption ratio) of about 10 −3 . The seeds provided fibrils with positive and much bigger VCD signal with g ∼10 −2 [8] . Large g ‐factors are typically explained by tighter packing of the peptide strands, more regular and larger‐scale crystal‐like order, and stronger coupling of the carbonyl chromophores., [,9a,10] Similar polymorphism due to the seeding was occasionally observed also in other experiments [7c,11] …”
Section: Introductionmentioning
confidence: 99%
“…As an alternate spectroscopic probe, we use circularly polarized luminescence (CPL) induced in achiral lanthanide compounds. Lately, we found that a Raman optical activity (ROA) spectrometer can be conveniently used to measure CPL, and that the signal is very sensitive to the environment of the lanthanide ion or a lanthanide complex [8,22] . While VCD is also sensitive to the longer‐range ordering, induced CPL senses the structure more locally, and thus provides convenient complementary information.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational circular dichroism (VCD), Raman optical activity (ROA), and circularly polarized luminescence (CPL) have become accessible and powerful techniques for investigating new chiral materials, biomolecules, cells, and soft tissues. Albeit, some lanthanide complexes [ 56 , 57 , 58 , 59 , 60 , 61 ] have already been measured and described using chiroptical methods, to the best of our knowledge, the VCD spectra of the chiral lanthanide–amino acid complexes have never been registered and interpreted. This study is devoted to the X-ray structural description of a series of lanthanide complexes with both enantiopure forms of alanine and to the interpretation of their VCD spectra measured as solids dispersed in the KBr pellets.…”
Section: Introductionmentioning
confidence: 99%